Higher Rates of Mensical Repair and Rim Preservation in Younger Patients with Discoid Lateral Menisci. Issue 5 (31st May 2022) - Kemper, W. Craig; Adsit, Lizzie R.; Cooper, Savannah; McKay, Scott; Latz, Kevin; Shea, Kevin; Fabricant, Peter; Beck, Jennifer; Schmale, Gregory; Tenfelde, Allison; Gupta, Andrew; Green, Dan; et al.
Background: Management of discoid meniscus in pediatric patients requires understanding of the presentation, associated risks, and appropriate techniques. Surgical treatment consists of saucerization, meniscus repair, meniscocapular stabilization, and, periodically, subtotal meniscectomy. The type of meniscal treatment is commonly determined during arthroscopy. Thus, surgeons, patients, and their parents/guardians must be prepared for a variety of surgical options. Hypothesis/Purpose: To compare intraoperative arthroscopic findings and treatment of discoid meniscus across pediatric age groups in a large multicenter quality improvement registry. Methods: A multi-center quality improvement registry (16 institutions, 26 surgeons) monitoring the safety of discoid meniscus surgery was reviewed. Audit processes using CPT codes were designed to ensure that all consecutive cases from 2018-2020 were prospectively entered on patients <19 years old into a HIPAA-compliant electronic platform. Patients were grouped into five groups based on age at time of surgery (<7, 7-10, 11-13, 14-16, >16). Demographic characteristics, discoid type, presence and type of tear, peripheral rim instability, repair technique, and partial meniscectomy/debridement beyond saucerization were reviewed. Chi-Square or Fisher's exact tests were used for categorical comparisons and a Kruskal-Wallis test for continuous comparisons. Results: 274 patients were identified (mean age 12.4 years, range 3-18; 47.3% females). Complete discoid meniscus and peripheral rim instability were found to be more prevalent in younger age groups (Table 1). Peripheral rim instability was noted in 55.5% of cases, most commonly in the posterior horn (24.8%). While a focal region of instability was most common, the youngest age group was more likely to have either multifocal instability or no instability. Repair was conducted more commonly in the younger cohorts, with a significant decrease in repair percentage (p=0.008) per age group. All-inside was the most common repair technique in all age groups. Partial meniscectomy/debridement beyond saucerization occurred more frequently in older age groups than younger age groups (p=.0002), including 38.4% of cases in the oldest age group (Table 2). Conclusion: Younger patients experienced a greater incidence of complete discoid menisci and meniscus repair in this age group and was more likely to have more than one area of rim instability. However, when meniscal resection beyond a saucerization was required, this was more likely to occur in older patients. Table 1. Age-Related Comparison of Discoid Meniscal Presentation and Treatment Table 2. Incidence of Additional Meniscal Resection Beyond Saucerization